Inclusive Urbanism. Advances in research, education and practice. - (:unkn) unknown (My University, 2020)
Die Publikation ist ein Ergebnis der strategischen Kooperation zwischen den Wissenschaftsstandorten Dresden und Delft. In drei Teile gegliedert enthält sie ausgewählte Beiträge der internationalen Konferenz „Urban Studies in Education and Research“, die Ende 2018 an der TU Dresden stattgefunden hat und sich den sozialen und gesellschaftlichen Herausforderungen, die mit zunehmenden Urbanisierungsprozessen einhergehen, widmete. Im ersten Teil geht es um den Begriff der Inklusion im Rahmen der städtebaulichen Forschung. Im zweiten Teil liegt der Schwerpunkt auf der universitären Lehre: Benötigt sie neue Unterrichtsformate, und wenn ja, wie können diese gestaltet werden, um den Studierenden den Einstieg in das Thema "inklusive Stadtplanung" zu erleichtern? In allen drei Teilen gibt es Beispiele aus der Praxis, denen der dritte Teil sodann komplett gewidmet ist.

Responding to the United Nations’ Sustainable Development Goal No. 11 to "make cities and human settlements inclusive, safe, resilient and sustainable", Inclusive Urbanism reveals a wide variety of approaches to promoting social inclusion. Questions of architecture and urbanism are considered alongside those of landscape design, urban geography and city planning. As the title suggests, the content is divided into three parts: research, education and practice. A conceptual framework is offered in the opening part along with a theoretical embedding of the term "inclusiveness". Here the discussion also encompasses the latest results of urban planning research. In the second part, the focus turns to university teaching. Do we need new teaching formats, and if so, how can these be designed to ease students into the topic of "inclusive urbanism"? The third part of the book offers diverse examples of spatial design, urban laboratories, planning and co-production processes, all presented with their respective possibilities for boosting inclusion. Consciously international in outlook, the book identifies practices in both the Global North and Global South. Inclusive Urbanism brings together selected contributions presented at an international conference on "Urban Studies" held at the TU Dresden in November 2018. The conference was jointly organized by the TU Dresden, the TU Delft, the Leibniz Institute of Ecological Urban and Regional Development in Dresden, the Czech Technical University of Prague and the Wroclaw University of Science and Technology.
Keywords: Stadtentwicklungsplanung; Stadtgestaltung; Inklusion; Partizipation; Bewohnerbeteiligung; Planungsbeteiligung; Planungstheorie; Planungspraxis; Planerausbildung; Stadtentwicklungsforschung